Oesophageal intrasquamous IgG4 deposits: an adjunctive marker to distinguish eosinophilic oesophagitis from reflux oesophagitis. Issue 7 (21st January 2016) - Zukerberg, Lawrence; Mahadevan, Krishnan; Selig, Martin; Deshpande, Vikram
Abstract : Aims: To explore the utility of an IgG4 immunohistochemical stain to help distinguish eosinophilic oesophagitis from gastroesophageal reflux disease. Methods and results: We examined 21 cases of eosinophilic oesophagitis and 25 cases of gastroesophageal reflux disease. The diagnosis of eosinophilic oesophagitis was based on the presence of oesophageal dysfunction, >15 eosinophils per high‐power field, and a lack of response to proton pump inhibitors. Gastroesophageal reflux disease showed intraepithelial eosinophils, but a clinical and/or histological response to proton pump inhibitor therapy. We also evaluated an additional cohort of 22 cases with intraepithelial eosinophils. Immunohistochemical staining for IgG4 was performed. Sixteen of 21 (76%) eosinophilic oesophagitis cases showed intrasquamous extracellular IgG4 deposits, whereas all 25 gastroesophageal reflux disease cases were negative. Mucosal IgG4‐positive plasma cells were identified in eosinophilic oesophagitis and gastroesophageal reflux disease cases in 58% and 40% of cases, respectively. Eosinophilic oesophagitis patients receiving treatment were less likely to be positive for intraepithelial IgG4 deposits (88% versus 53%). In the validation cohort, the sensitivity and specificity for eosinophilic oesophagitis were 88% and 100%, respectively. Conclusions: The presence of intrasquamous IgG4 deposits is a useful adjunctive marker in the distinction between eosinophilic oesophagitis and gastroesophageal reflux disease.